Medium-temperature degradable sand-carrying fiber as well as preparation method and application thereof

Through the preparation method of modified polylactic acid fiber, the problem of sand-carrying fiber deformation at high temperature and slow degradation at low temperature is solved, and the effect of stable sand-carrying and efficient degradation at medium temperature is achieved.

CN119640430APending Publication Date: 2025-03-18CHINA OILFIELD SERVICES LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411814487.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing sand-carrying fibers are difficult to maintain the fiber-shaped uniform dispersion in high-temperature formation environments, which affects the sand-carrying transportation capacity, and slow degradation in low-temperature environments affects subsequent mining.

Method used

Mixed polylactic acid with a modifier and then performed twin screw extrusion, blending granulation, vacuum drying and spinning treatment, medium temperature degradable sand-carrying fibers were prepared. The fiber was kept at 150°C for 2 hours without shrinking and deformation, and the degradation rate reached ≥95% within 30 days at 90°C.

Benefits of technology

It realizes the stability of the fiber and sand carrying functionality under a medium temperature environment, and quickly degrades at an appropriate temperature, without affecting subsequent formation mining, and no additional degradation agent is required.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640430A_ABST
    Figure CN119640430A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polylactic acid fiber preparation and the field of oil exploitation technology research, and particularly relates to a medium-temperature degradable sand-carrying fiber and a preparation method and application thereof. The preparation method of the medium-temperature degradable sand-carrying fiber comprises the following steps: S1, preparing polylactic acid, and drying; s2, uniformly mixing the polylactic acid and a modifier according to a ratio, adding the mixture into a double-screw extruder, and carrying out blending granulation and vacuum drying to obtain a spinning raw material; and S3, adding the spinning raw material into a spinning machine, carrying out melt extrusion on the spinning raw material through a screw rod, spraying the spinning raw material out of a spinneret plate through a spinning assembly, and carrying out winding, drafting and cutting to obtain the medium-temperature degradable sand-carrying fiber. The medium-temperature degradable sand-carrying fiber prepared by the preparation method disclosed by the invention can maintain no shrinkage deformation for 2 hours at 150 DEG C, and provides good sand-carrying functionality and supporting property; the degradation rate is greater than or equal to 95% after the temperature is maintained at 90 DEG C for 30 days, the degradation time can be shortened after the temperature is increased, and subsequent stratum mining is not influenced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polylactic acid fiber preparation and the research field of oil extraction technology, and specifically relates to a medium-temperature degradable sand-carrying fiber and a preparation method and application thereof. Background Art

[0002] In terms of stabilizing oil and increasing gas, "two deeps and one unconventional" (i.e. deepwater, deep ground, and unconventional oil and gas) are important areas and directions for future oil and gas development. For example, in recent years, 60%-70% of CNPC's newly added reserves are low-permeability and extra-low-permeability unconventional oil and gas resources, among which the complex formation environment has put forward higher requirements for working fluid materials. "Difficult and new" areas such as low-permeability and extra-low-permeability, deep high temperature, unconventional and offshore oil are waiting to be developed and utilized.

[0003] Hydraulic fracturing is an effective means of increasing production in low-permeability and ultra-low-permeability reservoirs. It uses a high-pressure ground pump group to pump high-pressure sand-carrying liquid into the formation to create cracks in the target formation. The fracturing fluid with proppant is injected into the crack, and the crack extends forward and is filled with proppant. After the pump is stopped, the liquid gradually returns to the ground and the proppant remains in the crack. In this way, a sufficiently long propped crack with high conductivity is formed in the formation to facilitate the penetration of oil and gas from the formation into the wellbore.

[0004] When fiber materials are added to the fracturing fluid, they will be evenly dispersed to form a spatial cross-linked network structure. By mechanically transporting, suspending and placing proppants, the sand-carrying capacity of the fracturing fluid can be improved, and the proppants can be transported to deeper cracks without being deposited at the bottom of the well or blocked in the near-well zone of the cracks, thereby achieving the best fracturing effect. If degradable fibers are used, they will naturally degrade after the fracturing and mining process is completed without affecting the subsequent process. In the entire fracturing process, both the functionality of sand carrying and transportation is achieved, and the operability of green degradation is achieved.

[0005] At present, the research on fracturing sand-carrying fibers mainly focuses on the sand-carrying capacity, conductivity, dispersion effect, etc. However, in different formation environments, fiber materials will undergo different changes. In high-temperature formation environments, it is difficult for polylactic acid fibers to maintain a uniform fiber dispersion in the fracturing fluid and maintain good sand-carrying capacity; in low-temperature formations, polylactic acid fibers degrade slowly, affecting subsequent mining. There are few studies on the temperature resistance and degradation of sand-carrying fibers at different temperatures.

[0006] The Chinese invention patent with publication number CN113981564A mentions a sand-carrying fiber, which mainly tests the sand-carrying capacity at room temperature and the degradation capacity at 90°C. However, in actual production, the sand-carrying process enters the formation environment, and the formation temperature is rarely at room temperature. In the case of high-temperature formations, the fiber shrinks and deforms, which may affect the sand-carrying capacity at the least and may block the pipeline at the worst. When 90°C is used to test the degradation, the degradation rate reaches 80% in 4 hours. Such a fast degradation rate is not conducive to the fracturing process.

[0007] The Chinese invention patent with publication number CN103703213A mentions the use of fibers that do not degrade at 80°C for well treatment. After the purpose of use is achieved, a degradation agent is added to promote the degradation of the fiber. In order to achieve short-term functionality and long-term degradation, the method of adding additional degradation agents is adopted, which increases costs and labor losses. Summary of the invention

[0008] In view of the defects of the prior art, the present invention provides a medium-temperature degradable sand-carrying fiber and a preparation method and application thereof.

[0009] The specific present invention is achieved through the following technical solutions:

[0010] A method for preparing medium-temperature degradable sand-carrying fiber, comprising:

[0011] S1 prepares polylactic acid and dries it;

[0012] S2: uniformly mixing the polylactic acid and the modifier according to a ratio, adding the mixture into a twin-screw extruder, and performing blending, granulation and vacuum drying to obtain a spinning raw material;

[0013] S3: adding the spinning raw material into a spinning machine, the spinning raw material is melt-extruded by a screw and ejected from a spinneret through a spinning assembly, and then is wound, drawn and cut to obtain a medium-temperature degradable sand-carrying fiber.

[0014] In the method for preparing the medium-temperature degradable sand-carrying fiber, the molecular weight of the polylactic acid is 80,000-200,000 g / mol, and the left-handed optical purity is 99.0-99.9%.

[0015] In the above-mentioned method for preparing the medium-temperature degradable sand-carrying fiber, the drying temperature is 40-80° C. and the drying time is 6-12 hours.

[0016] In the above-mentioned method for preparing the medium-temperature degradable sand-carrying fiber, the modifier includes one or more of polylactic acid polyol, lactide, and lactic acid.

[0017] In the above-mentioned method for preparing the medium-temperature degradable sand-carrying fiber, the mass ratio of the modifier to the mass ratio of the spinning raw material is 0.1%-4%.

[0018] The method for preparing the medium-temperature degradable sand-carrying fiber is as follows: the purity of the polylactic acid polyol is ≥99%; the hydroxyl value is 40-100 mgKOH / g; the acid value is ≤1.0 mgKOH / g; the molecular weight is 400-2500 g / mol; and the viscosity is 400-6000 mPa*s at 75°C, 27# rotor, and 200 rpm.

[0019] In the above-mentioned method for preparing the medium-temperature degradable sand-carrying fiber, the purity of the lactide is ≥98%, and the left-handed optical purity is ≥99%.

[0020] In the method for preparing the medium-temperature degradable sand-carrying fiber, the purity of the lactic acid is ≥98%, and the left-handed optical purity is ≥99%.

[0021] In the above-mentioned method for preparing the medium-temperature degradable sand-carrying fiber, the extrusion temperature of the twin-screw extruder is 170-200° C.; after vacuum drying, the moisture content of the spinning raw material is ≤200ppm.

[0022] In the method for preparing the medium-temperature degradable sand-carrying fiber, the temperature of the melt extrusion is 160-240°C; and the temperature of the spinning assembly is 210°C-250°C.

[0023] In the method for preparing the medium-temperature degradable sand-carrying fiber, the winding speed is 800-1500 m / min.

[0024] The above-mentioned method for preparing medium-temperature degradable sand-carrying fiber, the drawing is a two-pass water bath drawing; wherein, the first drawing temperature is 60-92°C, the drawing ratio is 2.2-4.2 times, the second drawing temperature is 60-92°C, and the drawing ratio is 1.05-2.0 times.

[0025] A medium-temperature degradable sand-carrying fiber is prepared by adopting the above-mentioned method for preparing the medium-temperature degradable sand-carrying fiber.

[0026] The above-mentioned medium-temperature degradable sand-carrying fiber has a fineness of 0.5-6D and a length of 3-12mm.

[0027] The above-mentioned medium-temperature degradable sand-carrying fiber can be evenly dispersed in a 150°C pure water environment and can remain without shrinkage and deformation for at least 2 hours; it can be evenly dispersed in a 90°C pure water environment and the degradation rate is ≥95% within 30 days.

[0028] The above-mentioned medium-temperature degradable sand-carrying fiber is used in oil well reservoir reconstruction.

[0029] The technical solution of the present invention has the following beneficial effects:

[0030] (1) The medium-temperature degradable sand-carrying fiber provided by the present invention can be maintained at 150°C for 2 hours without shrinking or deforming, providing good sand-carrying functionality and support; after being maintained at 90°C for 30 days, the degradation rate is ≥95%, and the degradation time will be shortened after the temperature increases, which will not affect the subsequent stratum mining;

[0031] (2) The medium-temperature degradable sand-carrying fiber provided by the present invention has good degradability and does not require additional degradation agents;

[0032] (3) The medium-temperature degradable sand-carrying fiber provided by the present invention has improved heat deformation resistance on the basis of the original polylactic acid sand-carrying fiber, and can achieve the purpose of short-term sand-carrying support and long-term natural degradation. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the following detailed description of the preferred embodiment.The drawings are only for the purpose of illustrating the preferred embodiments and are not to be construed as limiting the invention.

[0034] Figure 1 It is a cross-sectional microscopic image of the medium-temperature degradable sand-carrying fiber of the present invention;

[0035] Figure 2 It is a microscopic picture of the medium temperature degradable sand-carrying fiber of the present invention;

[0036] Figure 3 This is a diagram showing the dispersion effect of the medium-temperature degradable sand-carrying fiber of the present invention at room temperature;

[0037] Figure 4 The dispersion effect diagram of the medium-temperature degradable sand-carrying fiber prepared in Example 1 after being maintained at 150° C. for 2 hours;

[0038] Figure 5 The dispersion effect diagram of the fiber prepared in Comparative Example 4 after being maintained at 150°C for 2 hours. DETAILED DESCRIPTION

[0039] In order to fully understand the purpose, features and effects of the present invention, the present invention is described in detail through the following specific embodiments. Except for the following contents, the process method of the present invention adopts conventional methods or devices in the art. Unless otherwise specified, the following terms have the meanings commonly understood by those skilled in the art.

[0040] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe a feature or characteristic, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0041] Specifically, the present invention provides a method for preparing medium-temperature degradable sand-carrying fiber, comprising:

[0042] S1 prepares polylactic acid and dries it;

[0043] S2: uniformly mixing the polylactic acid and the modifier according to a ratio, adding the mixture into a twin-screw extruder, and performing blending, granulation and vacuum drying to obtain a spinning raw material;

[0044] S3: adding the spinning raw material into a spinning machine, the spinning raw material is melt-extruded by a screw and ejected from a spinneret through a spinning assembly, and then is wound, drawn and cut to obtain a medium-temperature degradable sand-carrying fiber.

[0045] The polylactic acid used in the present invention can be prepared according to the preparation method of the prior art or can be obtained through commercial purchase. The preparation method is, for example, to obtain polylactic acid by subjecting lactic acid monomer to a dehydration polycondensation reaction at high temperature; or to first convert lactic acid into lactide, and then to open the lactide ring and polymerize the lactide to form high molecular weight polylactic acid through a ring-opening polymerization reaction. The present invention does not specifically limit the preparation method of polylactic acid.

[0046] The twin-screw extruder is selected from one of the following: Norda TDS-30, Qijie SHJ-30, and Ruiya TSE-30.

[0047] In some preferred embodiments, the molecular weight of the polylactic acid is 80,000-200,000 g / mol, and the left-handed optical purity is 99.0-99.9%.

[0048] Optionally, the molecular weight of the polylactic acid is 80,000 g / mol, 90,000 g / mol, 100,000 g / mol, 110,000 g / mol, 120,000 g / mol, 130,000 g / mol, 140,000 g / mol, 150,000 g / mol, 160,000 g / mol, 170,000 g / mol, 180,000 g / mol, 190,000 g / mol or 200,000 g / mol.

[0049] Optionally, the left-handed optical purity of the polylactic acid is 99.1%, 99.2%, 99.3%, 99.4%, 99.5%, 99.6%, 99.7%, 99.8%, or 99.9%.

[0050] Through practice, when the molecular weight of polylactic acid is lower than the range of the present invention, it shrinks at 150°C, reducing the sand carrying effect; when the left-handed optical purity of polylactic acid is lower than the specified range of the present invention, the heat resistance will be reduced, and it will also shrink at 150°C.

[0051] More preferably, the molecular weight of the polylactic acid is 100,000-180,000 g / mol, and the left-handed optical purity is 99.3-99.5%.

[0052] In some preferred embodiments, the drying temperature is 40-80° C. and the drying time is 6-12 hours, thereby effectively removing moisture from the polylactic acid.

[0053] Optionally, the drying temperature may be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, or 80°C; the drying time may be 6h, 6.5h, 7h, 7.5h, 8h, 8.8h, 9h, 9.5h, 10h, 11.5h, or 12h.

[0054] The modifier plays a role in plasticizing and promoting degradation inside the fiber, increasing the distance between molecules and reducing the intermolecular forces. At the same time, the introduction of small molecules of the same family can increase the degradation rate of polylactic acid.

[0055] In some preferred embodiments, the modifier includes one or more of polylactic acid polyol, lactide, and lactic acid.

[0056] Further preferably, the purity of the polylactic acid polyol is ≥99%; the hydroxyl value is 40-100 mgKOH / g; the acid value is ≤1.0 mgKOH / g; the molecular weight is 400-2500 g / mol; and the viscosity is 400-6000 mPa*s at 75°C, 27# rotor, 200 rpm.

[0057] More preferably, the purity of the lactide is ≥98%, and the L-optical purity is ≥99%; the purity of the lactic acid is ≥98%, and the L-optical purity is ≥99%.

[0058] In some preferred embodiments, the mass ratio of the modifier to the spinning raw material is 0.1%-4%.

[0059] In practice, too much modifier will cause the melting point of the polymer to drop, affecting the heat resistance; while if the modifier ratio is lower than this range, it will affect the degradation rate of polylactic acid fiber.

[0060] Optionally, the mass ratio of the modifier to the spinning raw material is 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5% or 4.0%.

[0061] Further preferably, the mass ratio of the modifier to the spinning raw material is 0.3%-1%.

[0062] In some preferred embodiments, the extrusion temperature of the twin-screw extruder is 170-200° C.; after vacuum drying, the moisture content of the spinning raw material is ≤200 ppm.

[0063] Optionally, the extrusion temperature of the twin-screw extruder is 170°C, 175°C, 180°C, 185°C, 190°C, 195°C or 200°C; after vacuum drying, the moisture content of the spinning raw material is 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 100ppm, 110ppm, 120ppm, 130ppm, 140ppm, 150ppm, 160ppm, 170ppm, 180ppm, 190ppm or 200ppm.

[0064] Further preferably, the extrusion temperature of the twin-screw extruder is 180-190° C.; after vacuum drying, the moisture content of the spinning raw material is ≤100 ppm.

[0065] In some preferred embodiments, the temperature of the melt extrusion is 160-240°C; the temperature of the spinning assembly is 210°C-250°C.

[0066] Optionally, the temperature of the melt extrusion is 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C or 240°C; the temperature of the spinning assembly is 210°C, 220°C, 230°C, 240°C or 250°C.

[0067] Further preferably, the temperature of the melt extrusion is 230-240°C; the temperature of the spinning assembly is 230-240°C.

[0068] In some preferred embodiments, the winding speed is 800-1500 m / min.

[0069] Optionally, the winding speed is 800 m / min, 900 m / min, 1000 m / min, 1100 m / min, 1200 m / min, 1300 m / min, 1400 m / min or 1500 m / min.

[0070] Further preferably, the winding speed is 900m / min-1100m / min.

[0071] In some preferred embodiments, the stretching is a two-pass water bath stretching; wherein the first stretching temperature is 60-92°C, the stretching ratio is 2.2-4.2 times, and the second stretching temperature is 60-92°C, the stretching ratio is 1.05-2.0 times.

[0072] The drafting process is a process in which a fiber is stretched by an external force. When the fiber is stretched, the internal molecules will be stretched and arranged by force, and the heat will crystallize and shape, making the internal structure stable, thereby increasing the heat resistance and strength of the fiber.

[0073] Optionally, the first and second stretching temperatures may be 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 92°C respectively; the first stretching ratio is 2.2 times, 2.4 times, 2.6 times, 2.8 times, 3.0 times, 3.2 times, 3.4 times, 3.6 times, 3.8 times, 4.0 times or 4.2 times; the second stretching ratio is 1.05 times, 1.1 times, 1.2 times, 1.3 times, 1.4 times, 1.5 times, 1.6 times, 1.7 times, 1.8 times, 1.9 times or 2.0 times.

[0074] More preferably, the first stretching temperature is 65-75°C, the stretching ratio is 3.0-4.0 times, the second stretching temperature is 80-90°C, and the stretching ratio is 1.1-1.4 times.

[0075] On the other hand, the present invention provides a medium-temperature degradable sand-carrying fiber, which is obtained by the above-mentioned preparation method.

[0076] Figure 1 and Figure 2 The microscopic image of the medium temperature degradable sand-carrying fiber of the present invention is shown. According to the test, the fineness of the medium temperature degradable sand-carrying fiber of the present invention is 0.5-6D, the length is 3-12mm, and it can be evenly dispersed in a 150°C pure water environment and remain without shrinkage and deformation for at least 2 hours (see Figure 3 ); It can be evenly dispersed in a pure water environment at 90°C, and the degradation rate is ≥95% within 30 days. When the temperature rises, the degradation rate will accelerate.

[0077] In the preparation method of the medium-temperature degradable sand-carrying fiber of the present invention, the modifier, molecular weight, light purity, and drafting have a synergistic effect, and all play a role in heat resistance and degradation. These factors are not independent of each other, but multiple factors act on the internal structure of the fiber to achieve the desired purpose. Although the specific mechanism of action still needs further study, the functionality and degradability shown by the medium-temperature sand-carrying fiber product provided by the present invention have enabled it to be widely used in oil extraction.

[0078] Example

[0079] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods without specific conditions in the following examples are based on conventional methods and conditions.

[0080] Source of raw materials:

[0081] The polylactic acid with a molecular weight of 180,000 g / mol is TC L175;

[0082] The polylactic acid with a molecular weight of 110,000 g / mol is Natureworks 4302D;

[0083] The polylactic acid with a molecular weight of 250,000 g / mol is Natureworks 6400D;

[0084] The polylactic acid with a molecular weight of 50000 g / mol is Hisun 290;

[0085] Polylactic acid polyol was purchased from Shenzhen Guanghua Weiye Co., Ltd., brand: PLA2050B;

[0086] Lactide was purchased from Shenzhen Guanghua Weiye Co., Ltd.;

[0087] Lactic acid was purchased from Shenzhen Guanghua Weiye Co., Ltd.

[0088] Example 1: A method for preparing a medium-temperature degradable sand-carrying fiber

[0089] S1. Prepare the required polylactic acid and dry it.

[0090] S2. The polylactic acid and the modifier described in step S1 are mixed evenly and then added into a twin-screw extruder, blended and granulated, and dried to obtain a spinning raw material.

[0091] S3. The spinning raw material obtained in S2 is added into a spinning machine, melt-extruded through the screw of the spinning machine, and then ejected from the spinneret through the spinning assembly. Finally, medium-temperature degradable sand-carrying fiber is obtained after winding, drawing and cutting.

[0092] The molecular weight of the polylactic acid in step S1 is 180000 (g / mol), the left-handed optical purity is 99.5%, the drying temperature is 60° C., and the drying time is 8 hours.

[0093] The modifier in step S2 is polylactic acid polyol. The mass ratio of the polyol modifier to the spinning raw material is 1%, the purity of the polylactic acid polyol is 99.3%, its hydroxyl value is 53 mgKOH / g, the acid value is 0.76 mgKOH / g, the molecular weight is 1500 g / mol, and the viscosity is 800 mpa*s at 75°C, 27# rotor, and 200 rpm.

[0094] The twin-screw melt extrusion temperature in step S2 is 183° C., and the moisture content of the spinning raw material after vacuum drying is 78 ppm.

[0095] In step S3, the melting temperature is 230° C., the spinning assembly temperature is 235° C., and the winding speed is 1000 m / min.

[0096] The drafting process in step S3 is two-pass water bath drafting. The first drafting temperature is 68°C and the drafting ratio is 3.5 times; the second drafting temperature is 88°C and the drafting ratio is 1.2 times. The resulting fiber fineness is 1.8D and the fiber length is 6mm.

[0097] Example 2: A method for preparing a medium-temperature degradable sand-carrying fiber

[0098] S1. Prepare the required polylactic acid and dry it.

[0099] S2. The polylactic acid and the modifier described in step S1 are mixed evenly and then added into a twin-screw extruder, blended and granulated, and dried to obtain a spinning raw material.

[0100] S3. The spinning raw material obtained in S2 is added into a spinning machine, melt-extruded through the screw of the spinning machine, and then ejected from the spinneret through the spinning assembly. Finally, medium-temperature degradable sand-carrying fiber is obtained after winding, drawing and cutting.

[0101] The molecular weight of the polylactic acid in step S1 is 180,000 (g / mol) and the left-handed optical purity is 99.3%.

[0102] The polylactic acid in step S1 is dried at 60° C. for 8 hours.

[0103] The type of the modifier in step S2 is lactide. The mass ratio of the lactide modifier to the spinning raw material is 0.3%, the purity of lactide in the modifier is 99.1%, and the left-handed optical purity is 99.3%.

[0104] The twin-screw melt extrusion temperature in step S2 is 180° C., and the moisture content of the spinning raw material after drying is 105 ppm.

[0105] In step S3, the melting temperature is 230° C., the spinning assembly temperature is 235° C., and the winding speed is 1000 m / min.

[0106] The drafting process in step S3 is two-pass water bath drafting. The first drafting temperature is 72°C and the drafting ratio is 3.5 times; the second drafting temperature is 88°C and the drafting ratio is 1.2 times. The fiber fineness produced is 1.8D and the fiber length is 6mm.

[0107] Example 3: A method for preparing a medium-temperature degradable sand-carrying fiber

[0108] S1. Prepare the required polylactic acid and dry it.

[0109] S2. The polylactic acid and the modifier described in step S1 are mixed evenly and then added into a twin-screw extruder, blended and granulated, and dried to obtain a spinning raw material.

[0110] S3. The spinning raw material obtained in S2 is added into a spinning machine, melt-extruded through the screw of the spinning machine, and then ejected from the spinneret through the spinning assembly. Finally, medium-temperature degradable sand-carrying fiber is obtained after winding, drawing and cutting.

[0111] The molecular weight of the polylactic acid in step S1 is 180,000 (g / mol) and the left-handed optical purity is 99.3%.

[0112] The polylactic acid in step S1 is dried at 60° C. for 8 hours.

[0113] The type of modifier in step S2 is lactic acid. The mass ratio of the lactic acid modifier to the spinning raw material is 0.6%, the purity of the lactic acid is 98.9%, and the left-handed optical purity is 99%.

[0114] The twin-screw melt extrusion temperature in step S2 is 180° C., and the moisture content of the spinning raw material after drying is 105 ppm.

[0115] In step S3, the melting temperature is 230° C., the spinning assembly temperature is 235° C., and the winding speed is 1000 m / min.

[0116] The drafting process in step S3 is two-pass water bath drafting. The first drafting temperature is 72°C and the drafting ratio is 3.5 times; the second drafting temperature is 88°C and the drafting ratio is 1.2 times. The fiber fineness produced is 1.8D and the fiber length is 6mm.

[0117] Example 4: A method for preparing a medium-temperature degradable sand-carrying fiber

[0118] S1. Prepare the required polylactic acid and dry it.

[0119] S2. The polylactic acid and the modifier described in step S1 are mixed evenly and then added into a twin-screw extruder, blended and granulated, and dried to obtain a spinning raw material.

[0120] S3. The spinning raw material obtained in S2 is added into a spinning machine, melt-extruded through the screw of the spinning machine, and then ejected from the spinneret through the spinning assembly. Finally, medium-temperature degradable sand-carrying fiber is obtained after winding, drawing and cutting.

[0121] The molecular weight of the polylactic acid in step S1 is 110000 (g / mol) and the left-handed optical purity is 99.3%.

[0122] The polylactic acid in step S1 is dried at 60° C. for 8 hours.

[0123] The types of modifiers in step S2 are polylactic acid polyol and lactic acid. The mass ratio of polylactic acid polyol to spinning raw materials is 1%. The purity of lactic acid modifier stalactitic acid is 98.9%, and the left-handed optical purity is 99%; the mass ratio of lactic acid modifier to spinning raw materials is 0.2%. The purity of polylactic acid polyol is 99.3%, its hydroxyl value is 67mgKOH / g, its acid value is 0.51mgKOH / g, its molecular weight is 2000g / mol, and its viscosity is 45000mpa*s at 75°C, 27# rotor, and 200rpm.

[0124] The twin-screw melt extrusion temperature in step S2 is 180° C., and the moisture content of the spinning raw material after drying is 43 ppm.

[0125] In step S3, the melting temperature is 230° C., the spinning assembly temperature is 235° C., and the winding speed is 1000 m / min.

[0126] The drafting process in step S3 is two-pass water bath drafting. The first drafting temperature is 72°C and the drafting ratio is 3.5 times; the second drafting temperature is 82°C and the drafting ratio is 1.3 times. The resulting fiber fineness is 1.5D and the fiber length is 6 mm.

[0127] Comparative Example 1: A method for preparing medium-temperature degradable sand-carrying fiber (high molecular weight polylactic acid)

[0128] S1. Prepare the required polylactic acid and dry it.

[0129] S2. The polylactic acid and the modifier described in step S1 are mixed evenly and then added into a twin-screw extruder, blended and granulated, and dried to obtain a spinning raw material.

[0130] S3. The spinning raw material obtained in S2 is added into a spinning machine, melt-extruded through the screw of the spinning machine, and then ejected from the spinneret through the spinning assembly. Finally, medium-temperature degradable sand-carrying fiber is obtained after winding, drawing and cutting.

[0131] The molecular weight of the polylactic acid in step S1 is 250,000 (g / mol) and the left-handed optical purity is 99.3%.

[0132] The polylactic acid in step S1 is dried at 50° C. for 10 h.

[0133] The type of modifier in step S2 is lactic acid. The mass ratio of the lactic acid modifier to the spinning raw material is 0.6%, the purity of the lactic acid is 98.9%, and the left-handed optical purity is 99%.

[0134] The twin-screw melt extrusion temperature in step S2 is 180° C., and the moisture content of the spinning raw material after drying is 65 ppm.

[0135] In step S3, the melting temperature is 238° C., the spinning assembly temperature is 250° C., and the winding speed is 1000 m / min.

[0136] The drafting process in step S3 is two-pass water bath drafting. The first drafting temperature is 72°C and the drafting ratio is 3.5 times; the second drafting temperature is 88°C and the drafting ratio is 1.2 times. The fiber fineness produced is 1.8D and the fiber length is 6mm.

[0137] Comparative Example 2: A method for preparing medium-temperature degradable sand-carrying fiber (low molecular weight polylactic acid)

[0138] S1. Prepare the required polylactic acid and dry it.

[0139] S2. The polylactic acid and the modifier described in step S1 are mixed evenly and then added into a twin-screw extruder, blended and granulated, and dried to obtain a spinning raw material.

[0140] S3. The spinning raw material obtained in S2 is added into a spinning machine, melt-extruded through the screw of the spinning machine, and then ejected from the spinneret through the spinning assembly. Finally, medium-temperature degradable sand-carrying fiber is obtained after winding, drawing and cutting.

[0141] The polylactic acid in step S1 has a molecular weight of 50,000 (g / mol) and a left-handed optical purity of 99.3%.

[0142] The polylactic acid in step S1 is dried at 50° C. for 10 h.

[0143] The type of modifier in step S2 is lactic acid. The mass ratio of the lactic acid modifier to the spinning raw material is 0.6%, the purity of the lactic acid is 98.9%, and the left-handed optical purity is 99%.

[0144] The twin-screw melt extrusion temperature in step S2 is 180° C., and the moisture content of the spinning raw material after drying is 65 ppm.

[0145] In step S3, the melting temperature is 230° C., the spinning assembly temperature is 235° C., and the winding speed is 1000 m / min.

[0146] The drafting process in step S3 is two-pass water bath drafting. The first drafting temperature is 68°C and the drafting ratio is 3.5 times; the second drafting temperature is 82°C and the drafting ratio is 1.2 times. The fiber fineness produced is 1.8D and the fiber length is 6mm.

[0147] Comparative Example 3: A method for preparing medium-temperature degradable sand-carrying fiber (without adding a modifier)

[0148] S1. Prepare the required polylactic acid and dry it.

[0149] S2. Add the polylactic acid described in step S1 into a twin-screw extruder, granulate and dry to obtain a spinning raw material.

[0150] S3. The spinning raw material obtained in S2 is added into a spinning machine, melt-extruded through the screw of the spinning machine, and then ejected from the spinneret through the spinning assembly. Finally, medium-temperature degradable sand-carrying fiber is obtained after winding, drawing and cutting.

[0151] The molecular weight of the polylactic acid in step S1 is 180,000 (g / mol) and the left-handed optical purity is 99.3%.

[0152] The polylactic acid in step S1 is dried at 60° C. for 8 hours.

[0153] The twin-screw melt extrusion temperature in step S2 is 180° C., and the moisture content of the spinning raw material after drying is 105 ppm.

[0154] In step S3, the melting temperature is 230° C., the spinning assembly temperature is 235° C., and the winding speed is 1000 m / min.

[0155] The drafting process in step S3 is two-pass water bath drafting. The first drafting temperature is 72°C and the drafting ratio is 3.5 times; the second drafting temperature is 88°C and the drafting ratio is 1.2 times. The fiber fineness produced is 1.8D and the fiber length is 6mm.

[0156] Comparative Example 4: A method for preparing medium-temperature degradable sand-carrying fiber (without drafting)

[0157] S4. Prepare the required polylactic acid and dry it.

[0158] S5. The polylactic acid and the modifier described in step S1 are mixed evenly and then added into a twin-screw extruder, blended and granulated, and dried to obtain a spinning raw material.

[0159] S6. The spinning raw material obtained in S2 is added into a spinning machine, melt-extruded through the screw of the spinning machine, and then ejected from the spinneret through the spinning assembly. Finally, the medium-temperature degradable sand-carrying fiber is obtained after winding and cutting.

[0160] The molecular weight of the polylactic acid in step S1 is 180,000 (g / mol) and the left-handed optical purity is 99.3%.

[0161] The polylactic acid in step S1 is dried at 50° C. for 10 h.

[0162] The type of modifier in step S2 is lactic acid. The mass ratio of the lactic acid modifier to the spinning raw material is 0.6%, the purity of the lactic acid is 98.9%, and the left-handed optical purity is 99%.

[0163] The twin-screw melt extrusion temperature in step S2 is 180° C., and the moisture content of the spinning raw material after drying is 65 ppm.

[0164] In step S3, the melting temperature is 230° C., the spinning assembly temperature is 235° C., and the winding speed is 1000 m / min. The fineness of the produced fiber is 1.8D and the fiber length is 6 mm.

[0165] Performance Testing

[0166] The fibers prepared in each embodiment and comparative example were placed in pure water at 150°C and left to stand for 2 hours to observe the morphology of the fibers and calculate the hydrolysis rate. The results of the pure water degradation test are shown in Table 1.

[0167] As an example, Figure 4 and Figure 5 The dispersion effect diagrams of the fibers prepared in Example 1 and Comparative Example 4 after being maintained at 150° C. for 2 hours are respectively shown.

[0168] Table 1 Pure water degradation test results of samples

[0169] Serial number 150℃ / 2h heat resistance results 90℃ / 30 days hydrolysis results Example 1 Fiber dispersion, no deformation 95.3% Example 2 Fiber dispersion, no deformation 97.1% Example 3 Fiber dispersion, no deformation 95.9% Example 4 Fiber dispersion, no deformation 98.3% Comparative Example 1 Fiber dispersion, no deformation 72.5% Comparative Example 2 Fiber shrinkage and severe deformation 99.5% Comparative Example 3 Fiber dispersion, no deformation 81.3% Comparative Example 4 Fiber shrinkage and clustering 69.8%

[0170] From the experimental results, it can be seen that the addition of modifier can promote the degradation of the sand-carrying fiber well without affecting its heat-resistant deformation performance. High molecular weight PLA will cause the fiber to degrade slowly at 90°C, affecting the service life. Low molecular weight PLA fiber is not heat-resistant and easy to shrink and deform at 150°C. In the absence of modifier, PLA degrades slowly, and the fiber without drafting has no heat resistance effect, and shrinkage is most obvious at 150°C.

[0171] The present invention has been disclosed above with preferred embodiments, but those skilled in the art should understand that these embodiments are only used to describe the present invention and should not be understood as limiting the scope of the present invention. It should be noted that all changes and substitutions equivalent to these embodiments should be deemed to be included in the scope of the claims of the present invention. Therefore, the scope of protection of the present invention should be based on the scope defined in the claims.

Claims

1. A method for preparing a medium-temperature degradable sand-carrying fiber, characterized in that: include: S1 prepares polylactic acid and dries it; S2: uniformly mixing the polylactic acid and the modifier according to a ratio, adding the mixture into a twin-screw extruder, and performing blending, granulation and vacuum drying to obtain a spinning raw material; S3: adding the spinning raw material into a spinning machine, the spinning raw material is melt-extruded by a screw and ejected from a spinneret through a spinning assembly, and then is wound, drawn and cut to obtain a medium-temperature degradable sand-carrying fiber.

2. The method for preparing the medium-temperature degradable sand-carrying fiber according to claim 1, characterized in that: The molecular weight of the polylactic acid is 80000-200000 g / mol, and the left-handed optical purity is 99.0-99.9%.

3. The method for preparing the medium-temperature degradable sand-carrying fiber according to claim 1, characterized in that: The drying temperature is 40-80° C. and the drying time is 6-12 hours.

4. The method for preparing the medium-temperature degradable sand-carrying fiber according to claim 1, characterized in that: The modifier includes one or more of polylactic acid polyol, lactide, and lactic acid.

5. The method for preparing the medium-temperature degradable sand-carrying fiber according to claim 1, characterized in that: The mass ratio of the modifier to the spinning raw material is 0.1%-4%.

6. The method for preparing the medium-temperature degradable sand-carrying fiber according to claim 4, characterized in that: The polylactic acid polyol has a purity of ≥99%; a hydroxyl value of 40-100 mgKOH / g; an acid value of ≤1.0 mgKOH / g; a molecular weight of 400-2500 g / mol; and a viscosity of 400-6000 mpa*s at 75° C., 27# rotor, and 200 rpm.

7. The method for preparing the medium-temperature degradable sand-carrying fiber according to claim 4, characterized in that: The purity of the lactide is ≥98%, and the left-handed optical purity is ≥99%.

8. The method for preparing the medium-temperature degradable sand-carrying fiber according to claim 4, characterized in that: The purity of the lactic acid is ≥98%, and the left-handed optical purity is ≥99%.

9. The method for preparing the medium-temperature degradable sand-carrying fiber according to claim 1, characterized in that: The extrusion temperature of the twin-screw extruder is 170-200° C.; after vacuum drying, the moisture content of the spinning raw material is ≤200 ppm.

10. The method for preparing the medium-temperature degradable sand-carrying fiber according to claim 1, characterized in that: The temperature of the melt extrusion is 160-240°C; the temperature of the spinning assembly is 210-250°C.

11. The method for preparing the medium-temperature degradable sand-carrying fiber according to claim 1, characterized in that: The winding speed is 800-1500 m / min.

12. The method for preparing the medium-temperature degradable sand-carrying fiber according to claim 1, characterized in that: The drawing is a two-pass water bath drawing; wherein, the first drawing temperature is 60-92°C, the drawing ratio is 2.2-4.2 times, and the second drawing temperature is 60-92°C, the drawing ratio is 1.05-2.0 times.

13. A medium temperature degradable sand-carrying fiber, characterized in that: The fiber is prepared by the method for preparing the medium-temperature degradable sand-carrying fiber described in any one of claims 1 to 12.

14. The medium-temperature degradable sand-carrying fiber according to claim 13, characterized in that: The medium-temperature degradable sand-carrying fiber has a fineness of 0.5-6D and a length of 3-12 mm.

15. The medium-temperature degradable sand-carrying fiber according to claim 13, characterized in that: The medium-temperature degradable sand-carrying fiber can be uniformly dispersed in a 150° C. pure water environment and can remain without shrinkage and deformation for at least 2 hours; it can be uniformly dispersed in a 90° C. pure water environment and the degradation rate within 30 days is ≥95%.

16. Use of the medium-temperature degradable sand-carrying fiber according to any one of claims 13 to 15 in oil well reservoir reconstruction.

Citation Information

Patent Citations

  • Degradable fiber systems for well treatments and their use

    CN103703213A

  • Sand-carrying fiber and preparation and application thereof

    CN113981564A